Implementation of Quizizz Interactive Media to Increase Enthusiasm and Participation of Grade VI Students of SDN 3 Linggasari in Science Learning - Nova Abadul Fahmi; Subuh Anggoro (UM Purwokerto Press, 2025)
This study aims to describe the use of the Quizizz application in increasing student enthusiasm during science learning in grade 6 of SD Negeri 3 Linggasari. The method used is qualitative with data collection techniques through interviews and observations. The subjects of the study consisted of grade 6 students who participated in Quizizz-based learning. Data analysis was carried out by processing information obtained from interviews and observations, to obtain a clear picture of student enthusiasm in science learning. The results of the study showed a significant increase in student enthusiasm when using Quizizz as a science learning medium. Students showed positive responses, higher attention, and a desire to be actively involved in the learning process. Thus, the use of Quizizz has proven effective in creating a fun and interesting learning atmosphere, thereby increasing student motivation in learning. This study provides an important contribution to the development of more interactive and interesting learning methods for students.